Screening for MOG-IgG and 27 other anti-glial and anti-neuronal autoantibodies in "pattern II multiple sclerosis" and brain biopsy findings in a MOG-IgG-positive case: $hSven Jarius, Imke Metz, Fatima Barbara König, Klemens Ruprecht, Markus Reindl, Friedemann Paul, Wolfgang Brück and Brigitte Wildemann - Jarius, Sven; Metz, Imke; König, Fatima Barbara; Ruprecht, Klemens; Reindl, Markus; Paul, Friedemann; Brück, Wolfgang; Wildemann, Brigitte (Multiple sclerosis journal, 2016)
Background: Histopathological studies have revealed four different immunopathological patterns of lesion pathology in early multiple sclerosis (MS). Pattern II ...